Analysis of MAC Strategies for Underwater Applications - Ansari, S. (Kluwer Academic Publishers, 2015)
This study aims at analyzing the performance of protocols designed for the control of Medium Access in the underwater environment using Underwater Acoustic Wireless Sensor Networks (UW-ASNs). Oceans today, are playing an eminent part in monitoring climate, storing and releasing Carbon dioxide, supplying foodstuffs, and shipping. The sectors that can benefit most from this research are industries dealing with oil and gas, fisheries, UW instrumentation, armed forces, research and exploration bureaus, etc. Existing terrestrial Wireless Sensor Networks (WSN) Medium Access Control (MAC) protocol which mostly use radio waves for communications are unsuitable for underwater atmosphere. Underwater sensor networks (UWSNs) using acoustic wireless networking finds application in the supporting tools for such applications. The unique properties of the UW acoustic communication path necessitate the need for new efficient, reliable MAC protocols to meet the challenges of propagation delay, multipath and fading and excessive power absorption at higher frequencies etc. Owing to the typical properties of acoustic wave propagation in the underwater atmosphere, the energy efficiency in UW-ASN is badly affected by the long propagation delay and data packet collisions, which hinders the transmission of the data packets that enables us to achieve collective monitoring tasks. This paper, present MAC protocols tailored for UWANs, the classification of MAC protocols, the state of the art, environment characteristics, challenges, and performance metrics in terms of throughput, propagation delay, energy consumption and quantitative analysis of some selected protocols. It also gives an insight of some challenges and open issues for future works. The analysis was made on UAN-CW-MAC protocol and UAN-Aloha, to understand the shape of the throughput curves for the protocol. The simulations were performed on network simulator ns3 to obtain the throughput curves for uan-cw mac with 20 nodes and uan-Aloha with 2â15 sensor nodes with one sink. The results obtained are shown for 20 simulation runs for each node. Â© 2015, Springer Science+Business Media New York.